Therapeutic potential of melatonin and melatonergic drugs on K18‐hACE2 mice infected with SARS‐CoV‐2. Issue 1 (15th October 2021) - Cecon, Erika; Izabelle, Charlotte; Poder, Sophie Le; Real, Fernando; Zhu, Aiwei; Tu, Ly; Ghigna, Maria Rosa; Klonjkowski, Bernard; Bomsel, Morgane; Jockers, Ralf; Dam, Julie
Abstract: As the COVID‐19 pandemic grows, several therapeutic candidates are being tested or undergoing clinical trials. Although prophylactic vaccination against SARS‐CoV‐2 infection has been shown to be effective, no definitive treatment exists to date in the event of infection. The rapid spread of infection by SARS‐CoV‐2 and its variants fully warrants the continued evaluation of drug treatments for COVID‐19, especially in the context of repurposing of already available and safe drugs. Here, we explored the therapeutic potential of melatonin and melatonergic compounds in attenuating COVID‐19 pathogenesis in mice expressing human ACE2 receptor (K18‐ hACE2 ), strongly susceptible to SARS‐CoV‐2 infection. Daily administration of melatonin, agomelatine, or ramelteon delays the occurrence of severe clinical outcome with improvement of survival, especially with high melatonin dose. Although no changes in most lung inflammatory cytokines are observed, treatment with melatonergic compounds limits the exacerbated local lung production of type I and type III interferons, which is likely associated with the observed improved symptoms in treated mice. The promising results from this preclinical study should encourage studies examining the benefits of repurposing melatonergic drugs to treat COVID‐19 and related diseases in humans.